Motivasi dan Pengetahuan Investasi Generasi Zenial Dalam Meningkatkan Minat Investasi di Pasar Modal - Fuzi Waliyul Mujtahidin (Sains: Jurnal Manajemen dan Bisnis, 2023)
This study aims to determine the effect of investment motivation and investment knowledge on the interest in investing in the z generation. This research is a type of quantitative research using a survey method given to Generation Z. Determining the number of samples in this study were 100 respondents with the sampling method used was judgment sampling. The measurement tool in this study uses an interval scale of 1-5. Respondents gave answers in the range of answers from strongly disagree to strongly agree. Then, the analysis used is Regression Analysis. This analysis is assisted by using the SPSS program. The results of this study indicate that investment motivation has an effect on investment intention, while investment knowledge has no effect on investment intention.